2010
DOI: 10.1097/mjt.0b013e3181d5e4f3
|View full text |Cite
|
Sign up to set email alerts
|

Time to Onset of Neuropathic Pain Reduction: A Retrospective Analysis of Data From Nine Controlled Trials of Pregabalin for Painful Diabetic Peripheral Neuropathy and Postherpetic Neuralgia

Abstract: These retrospective analyses of daily mean pain scores from nine placebo-controlled trials of pregabalin at 150, 300, or 600 mg/day (pregabalin, n = 1205; placebo, n = 772) examined time to significant reduction of pain during the first 2 weeks of treatment of painful diabetic peripheral neuropathy and postherpetic neuralgia. Time to onset of reduction in pain-defined as the first day for which patients treated with pregabalin had significant reductions (P < 0.05) in mean pain score compared with the placebo g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 49 publications
5
42
0
1
Order By: Relevance
“…Since clinical benefit from gabapentinoids takes 3 or more days to develop in the clinic (Cheshire 2002;Sharma et al 2010), our studies were designed to replicate this situation in vitro. In confirmation of the results of Moore et al (2002), we found that gabapentinoids had little or no effect in spinal cord when applied acutely (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since clinical benefit from gabapentinoids takes 3 or more days to develop in the clinic (Cheshire 2002;Sharma et al 2010), our studies were designed to replicate this situation in vitro. In confirmation of the results of Moore et al (2002), we found that gabapentinoids had little or no effect in spinal cord when applied acutely (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Because neuropathic pain is characteristically resistant to the actions of conventional analgesics, treatment often involves the use of "antiallodynic" agents such as pregabalin (PGB) or gabapentin (GBP) (Moulin et al 2007). In the clinic, these drugs take at least 3 days to exert an effect (Cheshire 2002;Sharma et al 2010). Gabapentinoids are transported into neurons via the neutral amino acid transporter (Su et al 1995), where they interact with the ␣2␦-1 accessory subunits of voltage-gated calcium channels (Bauer et al 2009;Davies et al 2007;Field et al 2006;Gee et al 1996;Hendrich et al 2008;Patel et al 2013).…”
mentioning
confidence: 99%
“…In the case of primary afferent neurons, a2d is implicated in the relatively slow trafficking of a subunits of HVA-Ca 2+ channels from their site of synthesis in the cell body, along primary afferent axons, to their terminals in the spinal dorsal horn (Bauer et al, 2009). It is tempting to speculate that attenuation of this slow trafficking process by gabapentinoids corresponds to reports of their slow onset of action in neuropathic pain patients (Cheshire, 2002;Stacey et al, 2008;Sharma et al, 2010), but, as discussed in Rate of Onset of Gabapentinoid Effect, we think this is unlikely to be the case.…”
Section: +mentioning
confidence: 99%
“…Despite their rapid efficacy in animal models of neuropathic pain (Hunter et al, 1997;Field et al, 2006;Narita et al, 2012;Kumar et al, 2013;Alles and Smith, 2016;Alles et al, 2017), several reports indicate that GBP effects in clinical pain management take a day or more to develop (Cheshire, 2002;Stacey et al, 2008;Sharma et al, 2010;Rauck et al, 2013).…”
Section: Rate Of Onset Of Gabapentinoid Effectmentioning
confidence: 99%
“…In an analysis of data from 9 placebo-controlled trials in patients with neuropathic pain due to diabetic peripheral neuropathy or postherpetic neuralgia, the time to significant pain relief usually occurred within 2 days of initiating treatment with pregabalin. 19 Similarly, the time to significant relief of pain-related sleep interference was estimated at 1 to 2 days in a retrospective analysis of 16 placebo-controlled trials of pregabalin in patients with painful diabetic peripheral neuropathy or post-herpetic neuralgia. 20 Timing of pregabalin's therapeutic effect was also examined in a retrospective analysis of 4 placebo-controlled trials in patients with fibromyalgia, whereby the time to significant improvement in pain and sleep quality was estimated at 1 to 2 days.…”
Section: Discussionmentioning
confidence: 99%